Studi Analisis Akurasi Perhitungan Awal Waktu Shalat Menggunakan Universal Astrolabe - Hadi, Imron (Universitas Islam Negeri Mataram, 2022)
Universal Astrolabe is a type of Astrolabe that can be used in any region or latitude. This paper examines the accuracy of the Universal Astrolabe in determining the start of the five daily prayer times (Fajr, Zuhur, Asr, Maghrib and Isha). The purpose of this study was to determine the accuracy of the calculation method for determining the beginning of prayer times using the Universal Astrolabe. Astrolabe is one of the classical astronomical instruments that describes the celestial sphere in two dimensions and was originally used to determine the position of the Sun. Astrolabe comes from the Greek language which consists of the word